Tourism Price Competition Index for National Destinations - Göral, Ramazan; Akgöz, Erkan (Journal of Tourism Management Research, 2017)
Visitors are aware towards touristic goods and service prices and take cost of tourism package involving touristic goods and services into consideration in decision of choosing destination. Addressing cost of touristic goods and service package with destination choice and touristic demand made price competition a current issue in tourism. The destination that has comparative price advantage among alternative destinations is accepted as having high tourism price competition power. In this scope the first aim of our study is to develop a method that can make tourism package price comparison in rival national destinations. The second aim on the other hand depending upon the first aim is to form price competition towards alternative national destinations. In this scope basing on Household Budget Study of Turkish Statistical Institute (TÜİK), tourism package prices of the most important 4 destinations of Turkey were compared and price competition index was calculated.